Acculturation of Culture and Religion in Religious Moderation of the Amanuban Indigenous Community: An SDGs Perspective - Yahya Nikmat Nobisa; Akhsanul In’am; Moh. Mahfud Effendi; Syarifuddin Darajad; Indah Febriana As’ari Putri (Profetika: Jurnal Studi Islam, 2026)
Objective: This study aims to analyze the process of cultural and religious acculturation as a practice of religious moderation in strengthening the social identity and sustainability of the life of the Amanuban indigenous community in South Central Timor Regency (TTS). Theoretical Framework: This study is based on the theory of cultural acculturation, the concept of religious moderation, and the symbolic interactionism approach that views social identity and religious practices as the result of the construction of meaning through symbolic interaction in the context of local culture. Literature Review: The literature review shows that the integration of culture and religion plays an important role in maintaining social harmony in plural societies, but studies that directly link it to the sustainability of local identity and social development are still relatively limited. Methods: This study uses a descriptive qualitative approach with a phenomenological design. Data were collected through in-depth interviews with traditional and religious leaders, participatory observation of socio-religious practices, and documentation studies. Data analysis was carried out thematically to explore the life experiences, social meanings, and symbolic values ​​inherent in the practices of cultural and religious acculturation of the Amanuban community. Results: The results of the study indicate that cultural and religious acculturation serve as an effective social mechanism in shaping the character of an inclusive, tolerant, and harmony-oriented society among religious communities. Local values ​​such as feto-mone and natoni act as an integrative medium that bridges differences in beliefs and strengthens the collective identity of the community without negating the basic principles of religious teachings. Implications: These findings confirm that cultural and religious acculturation contribute to the achievement of the Sustainable Development Goals (SDGs), especially SDG 16 through strengthening peace and social cohesion, and SDG 11 through preserving cultural identity and community sustainability. Novelty: The novelty of this study lies in the phenomenological analysis of cultural and religious acculturation as a strategy for sustainable religious moderation in facing modern social dynamics.